Analisis Kebutuhan Tenaga Kerja Front Office Departmen di The Astari Villa and Residence Jimbaran Bali - Kharismayana, I Komang Yudi; Sri, Anak Agung Putri; Suarka, Fanny Maharani (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 1 (2021): Vol.5,No.1,2021DO - 10.24843/JKH.2021.v05.i01.p04, 2021)
The background of this research is because the high of workload on the employees that impactthe quality of service or work from FO Spv, reception, belldriver, and reservation. That will cause the decrease theservice rate, the level of work concentration, excessive work hours, and the attention to the guests will be lessened, and it will probably make guests feel disappointed about the services provided by the Front Office Department. The purpose of this study is to discover the workload and the total manpower that should be needed at the Front Office Department at The Astari Villa & Residence Jimbaran. The methods in collecting the data were by doing observation, interview, and did a questionnaire. In analyzing the data was used descriptive qualitative to describe the job of the Front Office Department, and used quantitative methods to answer the problem of the study in this research. The result of the data analysis shows the workload from the entire section of the Front Office Department at The Astari Villa & Residence Jimbaran encounter with lack of manpower which has different quantities of manpower in every section, that decreasing the quality of service to the guests. It could be seen from the guests’ comments to the service that provided by the Front Office Department, were dominated with ‘Average’ rate. To increase the service for the guests, there should be also increased the amount of manpower in every section of the Front Office Department. The actual total manpower needed are 2 for FO Spv, 4 for reception, 2 for belldriver, and 1 for the reservation to completing the duties and be responsible for their work. But, due to the emptiness of the reservation section, they need to hire a new manpower to fulfill the section. The additional of manpower in every section will probably help the operational duties of Front Office Department goes well and could give the guests the best and fast service .   Keywords: workload, labor needs, front office